2011
DOI: 10.1057/jors.2010.156
|View full text |Cite
|
Sign up to set email alerts
|

Finding common weights based on the DM's preference information

Abstract: Data Envelopment Analysis (DEA) is basically a linear programming based technique used for measuring the relative performance of organizational units, referred to as Decision Making Units (DMUs). The flexibility in selecting the weights in standard DEA models deters the comparison among DMUs on a common base. Moreover, these weights are not suitable to measure the preferences of a decision maker (DM). For dealing with the first difficulty, the concept of common weights was proposed in the DEA literature. But, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The numerical results along with some qualitative assessments confirm the superiority of the proposed method when compared with the previously developed relevant techniques. Recently, finding common weights based on the DM's preference information is addressed by Jahanshahloo et al [38] in the DEA literature that measures the preferences of decision maker when generating the common weights. Accordingly, incorporating the inventory manager's preferences in a new model to derive common weights is proposed for future research in the context of MCIC.…”
Section: Discussionmentioning
confidence: 99%
“…The numerical results along with some qualitative assessments confirm the superiority of the proposed method when compared with the previously developed relevant techniques. Recently, finding common weights based on the DM's preference information is addressed by Jahanshahloo et al [38] in the DEA literature that measures the preferences of decision maker when generating the common weights. Accordingly, incorporating the inventory manager's preferences in a new model to derive common weights is proposed for future research in the context of MCIC.…”
Section: Discussionmentioning
confidence: 99%
“…The entropy of single output is defined to be 0 in Table 4; Step 5: Determining the importance degree of optimal weights as it is shown in Table 4; Step 6: Determining the common weights. By formula (18) we can get the common weights are = 1.2239, = 0.9681 and = 0.8248. Then the efficiency evaluation result is provided in Table 5.…”
Section: Illustration Examplementioning
confidence: 99%
“…Ramon et al [12,13] extended their research on the cross-efficiency evaluation into the common weights DEA method based on the idea of reducing differences between profiles of weights. Some other techniques have also been introduced into the DEA method for determining common weights, such as goral programming [14], regression analysis [15], robust optimization [16] and so on [17][18][19][20]. Applications of the common weights DEA models can be found in economy evaluation [21], technology selection [22], resource allocation [23], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Jahanshahloo et al [18] suggested two methods to determine CSWs based on comparing ideal line and special line. Jahanshahloo et al [21] implemented Zionts-Wallenius technique to find CSWs based on the DM's preference information. Sun et al [39] introduced two models from MADA viewpoint for searching CSWs which is obtained based on applying ideal and anti-ideal units.…”
Section: Introductionmentioning
confidence: 99%